Peningkatan Kreativitas Anak Melalui Metode Bermain Plastisin Pada Anak Usia 5-6 Tahun - Manggali, Lia Ratu; Zultiar, Indra; Munajat, Asep (Calakan : Jurnal Sastra, Bahasa, dan Budaya, 2025)
This study aims to enhance the creativity of children aged 5-6 years through the playdough method at PAUD Ratu, Pasiripis Village, Surade District, Sukabumi Regency. The research employs Classroom Action Research (CAR) conducted in two cycles. Each cycle consists of planning, implementation, observation, and reflection. The results indicate that the playdough method is effective in improving children's creativity. Initially, only 33.33% of children met the expected development criteria. After the first cycle, the percentage increased to 66.67%, and in the second cycle, it reached 83.33%. The conclusion of this study is that playdough can be an effective method to enhance early childhood creativity.